Innovating writing centers and online writing labs outside North America. - Tan , Bee Hoon (2011)
This study highlights the writing difficulty of tertiary students in ESL or EFL contexts. It describes two successful innovations, writing center and online writing lab, initiated by North American institutions of higher learning to intervene in the writing crisis. Enquiries on initiative efforts by a few Asian and European universities in innovating writing centers and online writing labs are conducted through their websites, practitioners' reports, and e-mail interviews. The purpose is to learn from their common and differing practices to inform faculties who are interested in setting up their own institutional writing centers and online writing labs. Based on the Asian and European writing centers investigated, several generalizations can be drawn that may provide some insights for innovating writing centers and online writing labs in Asia.